Meteorological comfort indices to assess extreme warmness in southwest, Nigeria (2019)
2015, 2016 and 2017 have been confirmed the three warmest years on record and the degree of warming during these three years has been exceptional. Extremes of heat and cold environmental conditions have been known to be very detrimental to the health and comfort of humans. The severity of these adverse effects is often local and varies from one place to another though they are happening on a global scale therefore Temperature variation, Heat Index (HI) temperature and Dew Point Temperature (DPT) ( Meteorological comfort indices) were used to assess the effect of this condition in southwest, Nigeria. Air temperature and Humidity data were collected from meteorological stations situated in the southwestern states selected for study and was processed using the rule of Thumb for DPT calculations as expressed by Lawrence (2005) and Steadman (1979) formula simplified by Rothfusz’ model (1990) for HI temperature. The data analysis was done using Microsoft Excel Package and Statistical Package for the Social Sciences (SPSS), the following results were obtained: Elevation may affect temperature yet during extreme warmness other factors can have a greater influence on temperature and meteorological comfort indices used to assess extreme warmness in southwest Nigeria from this study showed greater impacts thus: Heat Index Temperature has highest values in Lagos State, while Dew Point Temperature have highest values in Ogun state. None of these extreme warmness measuring variables seem to be solely in favour of state Location in terms of coordinates and elevation; this suggests more anthropogenic influence forming the characteristics of the states to geographic locations of the states however, between the start year of extreme warmness (2015) and 2017, HI temperature showed a significant increase while average DPT did not really change during the period of extreme warmness.